PEMODELAN MATEMATIK PERUBAHAN PARAMETER MUTU KERUPUK SELAMA PENGGORENGAN DENGAN PASIR [Mathematical Modeling of Quality Parameter Changes of Chips During Sand Frying] - Siswantoro - -; Budi - Rahardjo; Nursigit - Bintoro; Pudji - Hastuti (Jurnal Teknologi dan Industri Pangan, 2011)
Chip is a preferred food by all economic levels of society. Before consumption, chip is prepared by frying. There are different kinds of frying methods; one of them is conducted using sand as the heat transfer medium, known as “hot sand frying". Frying using sand is interesting because of the specific characteristics of the final product. First, the chip is not oily, so that it does not easily become rancid. Secondly, chip prepared by sand frying is easily returned to its crunchiness by heating it at medium temperature (between 35 - 450C). The general purpose of this research is to develop a frying process using sand as the heat transfer medium. The specific purpose of this research is to develop a mathematical model to explain the quality parameter changes during sand frying. This laboratory based experiment was conducted using river sand and ferric sand as the medium for hot transfer and raw chip as the sample food. Equipment used include tools for measuring physical and thermal properties, a sand frying machine, tachometer, thermocouple, data logger, interface, and a personal computer. The results show that the average deviation of the predicted values is less than 10%., which suggests that the proposed mathematical model has a reliable precision level.